A Model of Dynamic Visual Attention for Object Tracking in Natural Image Sequences - Ouerhani, Nabil; Hügli, Heinz (My University, 2003)
Visual attention is the ability to rapidly detect the interesting parts of a given scene on which higher level computer vision tasks can focus. This paper reports a computational model of dynamic visual attention which combines static and dynamic features to detect salient locations in natural image sequences. Therefore, the model computes a map of interest—saliency map—related to static features and a saliency map derived from dynamic scene features and then combines them into a final saliency map, which topographically encodes stimulus saliency. The information provided by the model of attention is then used by a tracking method to attentively track the interesting features in the scene. The experimental results, reported in this work refer to real color image sequences. They clearly validate the reported model of dynamic visual attention and show its usefulness in guiding the tracking task.